Bartnictwo na ziemi bytowskiej w okresie nowożytnym = Beekeeping in Bütow land in the modern period - Kargul, Michał (1979- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Even though beekeeping is one of the fields of modern forestry that is most fully described in the literature, it is still in need of detailed research. Bütow Land, which was organized as a princely domain in the Times of the Pomeranian princes and as a non-town starosty in the times of the Republic, is a district concerning which we have relatively much information concerning the breeding of forest bees in that period.
Keywords: Pszczelnictwo - Polska; Bytów (woj. pomorskie; okręg) - rzemiosło.; Polska - 16-18 w.